Application of Neuman's Systems Model on Anxiety of Older Adults Waiting for Colonoscopy - Fatemeh Larijani; Zahra Fotokian; Mehri Jahanshahi; Sahar Risman Tabi (Kashan University of Medical Sciences, 2021)
Background: Older adults waiting for colonoscopy are anxious due to the lack of knowledge about the procedure, its preparations, and aftercare. Objectives: The aim of this study was to evaluate the effect of the Neuman systems model (NSM) on anxiety of older adults waiting for colonoscopy. Methods: A pre- and postintervention study was conducted on 72 older adults who were waiting for colonoscopy. The participants were randomly allocated to either a control (n = 36) or an intervention group (n = 36). The intervention was performed in four steps, namely determining the potential and actual stressors, setting the goals, nursing interventions, and evaluation, according to the four-step nursing process in the NSM. A need assessment checklist based on the NSM and the Geriatric Anxiety Scale was completed before and after the intervention. Data analysis was performed using Fisher's exact, independent, and paired t-tests. Results: At baseline, the mean score of total anxiety was 35.66 ± 7.58 in the intervention group and 35.29 ± 6.52 in the control group. After the intervention, these values changed to 26.71 ± 7.48 and 34.06 ± 7.23. Before the intervention, there was no statistically significant difference between the anxiety scores of the two groups in cognitive, affective, and somatic dimensions and total anxiety scores (P > 0.05). However, after the intervention, statistically significant differences were found between the two groups in the mean scores of the aforementioned components (P < 0.001). Conclusion: Implementing an educational program based on NSM reduced anxiety in older adults waiting for colonoscopy. Nurses should be trained about the NSM to be able to use similar programs in reducing the anxiety of patients waiting for colonoscopy.